Penggunaan Aplikasi Mobile Technology untuk Deteksi Breeding Place Pencegahan Demam Dengue: Literature Review - Agni Laili Perdani; Ratna Nurul Komariah; Dewi Srinatania (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
The existence of a breeding place have threefold greater risk to the DHF incidence. The participation of mosquito monitoring interpreters (JUMANTIK) by using an Android-based smartphone application functions play significant role to inform the location of interactive breeding places with the latest data updates. Aim of this study to analyze the use of mobile technology applications in the detection of dengue breeding places with the PRISMA method approach. Method used in this study is s a literature review . Database used Google Scholar, Pubmed and Proquest. The keywords used are the combination